Reliability of nanoscale circuits and systems methodologies and circuit architectures - Stanisavljevic, Milos; Schmid, Alexandre; Leblebici, Yusuf; SpringerLink (Online service). (New York Springer New York, 2011)
Reliability of Nanoscale Circuits and Systems: Methodologies and Circuit Architectures Milos Stanisavljevic Alexandre Schmid Yusuf Leblebici Future integrated circuits are expected to be made of emerging nanodevices and their associated interconnects, but the reliability of such components is a major threat to the design of future integrated computing systems. Reliability of Nanoscale Circuits and Systems: Methodologies and Circuit Architectures confronts that challenge. The first part discusses the state-of-the-art of the circuits and systems as well as the architectures and methodologies focusing the enhancement of the reliability of digital integrated circuits. It proposes circuit and system level solutions to overcome high defect density and presents reliability, fault models and fault tolerance. It includes an overview of nano-technologies that are considered in the fabrication of future integrated circuits and covers solutions provided in the early ages of CMOs as well as recent techniques. The second part of the text analyzes original circuit and system level solutions. It details an architecture suitable for circuit-level and gate-level redundant modules implementation and exhibiting significant immunity to permanent and random failures as well as unwanted fluctuation and the fabrication parameters. It also proposes a novel general method enabling the introduction of fault-tolerance and evaluation of the circuit and architecture reliability. And the third part proposes a new methodology that introduces reliability in existing design flows. That methodology consists of partitioning the full system to design into reliability optimal partitions and applying reliability evaluation and optimization at local and system level.
Introduction -- Reliability, Faults and Fault Models -- Nanotechnology and Nanodevices -- Fault-Tolerant Architectures and Approaches -- Reliability Evaluation Techniques -- Averaging Design Implementations -- Statistical Evaluation of Fault-Tolerance Using Proability Density Functions -- System Level Reliability Evaluation and Optimization -- Summary and Conclusions -- References.
Electronic reproduction.
Keywords: Nanoelectromechanical systems -- Reliability; Nanoelectronics; Electronic books